2021
DOI: 10.1111/bcp.14888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CES1 genetic variation on enalapril steady‐state pharmacokinetics and pharmacodynamics in healthy subjects

Abstract: A previous in vitro study demonstrated the CES1 genetic variant, G143E (rs71647871), significantly impaired enalapril activation. Two previous clinical studies examined the impact of G143E on single-dose enalapril PK (10 mg); however, the results were inconclusive. A prospective, multi-dose, pharmacokinetics and pharmacodynamics (PK/PD) study was conducted to determine the impact of the CES1 G143E variant on enalapril steady-state PK and PD in healthy volunteers. Methods: Study participants were stratified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…In particular, many investigations have explored the effects of genetic polymorphisms on the activity and expression of CES1 and ensuing impacts on the PK and clinical outcomes of CES1 substrate drugs. However, while several CES1 genetic variants have been found to affect CES1 activity and expression, only the nonsynonymous variant G143E showed consistent effects on both the PK and PD of CES1 substrates such as methylphenidate, clopidogrel, and enalapril 13,14,27–31 . It should be noted that the G143E variant impairs CES1 catalytic activity without altering CES1 expression, and hepatic CES1 expression varies markedly among individuals having the same G143E genotype 10,11 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In particular, many investigations have explored the effects of genetic polymorphisms on the activity and expression of CES1 and ensuing impacts on the PK and clinical outcomes of CES1 substrate drugs. However, while several CES1 genetic variants have been found to affect CES1 activity and expression, only the nonsynonymous variant G143E showed consistent effects on both the PK and PD of CES1 substrates such as methylphenidate, clopidogrel, and enalapril 13,14,27–31 . It should be noted that the G143E variant impairs CES1 catalytic activity without altering CES1 expression, and hepatic CES1 expression varies markedly among individuals having the same G143E genotype 10,11 .…”
Section: Discussionmentioning
confidence: 91%
“…It should be noted that the G143E variant impairs CES1 catalytic activity without altering CES1 expression, and hepatic CES1 expression varies markedly among individuals having the same G143E genotype 10,11 . Similarly, the PK of CES1 substrate drugs differed significantly among subjects in the same G143E genotype group 28,30–32 . Therefore, beyond the G143E variant, the identification of a reliable biomarker of hepatic CES1 protein expression is of significant clinical interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the activity of the enzyme can critically depend on the genetic variants of the CES1 gene. Accordingly, markers in the CES1 gene play a role in interindividual differences in the metabolism and effect numerous drugs that are substrates of this enzyme [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Thus, single nucleotide polymorphisms (SNPs) are known in the CES1 gene that lead to a change in the activity of the enzyme, for example, G143E (rs71647871) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and variant 1168-33C>A in intron 10 (rs2244613) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%